2019 IEEE/CVF International Conference on Computer Vision Workshop (ICCVW) 2019
DOI: 10.1109/iccvw.2019.00055
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Inference via Weakly-Supervised Learning using a Large Collection of Negative MRI

Abstract: Recent advances in medical imaging techniques have led to significant improvements in the management of prostate cancer (PCa). In particular, multi-parametric MRI (mp-MRI) continues to gain clinical acceptance as the preferred imaging technique for non-invasive detection and grading of PCa. However, the machine learning-based diagnosis systems for PCa are often constrained by the limited access to accurate lesion ground truth annotations for training. The performance of the machine learning system is highly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…In contrast, medical imaging modalities in radiology and nuclear medicine exhibit much lower inter-sample variability, where the spatial content of a scan is limited by the underlying imaging protocols and human anatomy. In agreement with recent studies [2][3][4], we hypothesize that variant architectures of U-Net can exploit this property via an explicit anatomical prior, particularly at the task of csPCa detection in bpMRI. To this end, we present a probabilistic population prior P , constructed using radiologically-estimated csPCa annotations and CNN-generated prostate zonal segmentations of 700 training samples.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, medical imaging modalities in radiology and nuclear medicine exhibit much lower inter-sample variability, where the spatial content of a scan is limited by the underlying imaging protocols and human anatomy. In agreement with recent studies [2][3][4], we hypothesize that variant architectures of U-Net can exploit this property via an explicit anatomical prior, particularly at the task of csPCa detection in bpMRI. To this end, we present a probabilistic population prior P , constructed using radiologically-estimated csPCa annotations and CNN-generated prostate zonal segmentations of 700 training samples.…”
Section: Introductionsupporting
confidence: 89%
“…Meanwhile, machine learning models can adapt several techniques, such as reference coordinate systems [11,12] or anatomical maps [2], to integrate domain-specific priori into CNN architectures. In recent years, the inclusion of zonal priors [4] and prevalence maps [3] have yielded similar benefits in 2D CAD systems for prostate cancer.…”
Section: Related Workmentioning
confidence: 99%
“…23,40,45 To test generalizability, some studies trained AI models using one group of patients, and tested on a different group, including patients with different disease distributions 50,51 or different label types. 40,59 Due to the difficulty in acquiring large data sets of pathology-confirmed cancer labels to train AI models, a study 67 trials (see Section "Challenges in AI for PCa" for more details).…”
Section: Therapeutic Advances In Urologymentioning
confidence: 99%
“…Parallel to recent studies in medical image computing (Gibson et al, 2018;Dalca et al, 2018;Wachinger et al, 2018;Cao et al, 2019b) on infusing spatial priori into CNN architectures, we hypothesize that M 1 can benefit from an explicit anatomical prior for csPCa detection in bpMRI. To this end, we construct a probabilistic population prior P, as introduced in our previous work (Saha et al, 2020).…”
Section: Anatomical Priormentioning
confidence: 81%
“…The study demonstrated that the inclusion of PZ and TZ segmentations can introduce an average increase of 5.3% detection sensitivity, between 0.5-2.0 false positives per patient. In a separate study, Cao et al (2019b) constructed a probabilistic 2D prevalence map from 1055 MRI slices. Depicting the typical sizes, shapes and locations of malignancy across the prostate anatomy, this map was used to weakly supervise a 2D U-Net for PCa detection.…”
Section: Related Workmentioning
confidence: 99%